2014
DOI: 10.3109/14767058.2014.889113
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia and severe perineal tears: a literature review and large cohort study

Abstract: During the study period, 61,308 eligible women gave birth, 31,631 (51.6%) of whom received epidural analgesia. SPT occurred in 0.3% of births. Deliveries with epidural had significantly higher rates of primiparity, induction and augmentation of labor, prolonged second stage of labor, instrumental births and midline episiotomies. The univariate analysis showed a significant association between the use of epidural and SPT (OR: 1.78, 95% CI: 1.34-2.36); however, this association disappeared when parity was introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 25 publications
5
40
1
Order By: Relevance
“…This is supported by Loewenberg‐Weisband et al38 who also found that epidural analgesia is not associated with severe perineal lacerations, once confounding factors were controlled for. Other studies found a protective effect of epidural analgesia and therefore suggest epidural should not be considered an independent risk factor 28, 30…”
Section: Discussionmentioning
confidence: 57%
“…This is supported by Loewenberg‐Weisband et al38 who also found that epidural analgesia is not associated with severe perineal lacerations, once confounding factors were controlled for. Other studies found a protective effect of epidural analgesia and therefore suggest epidural should not be considered an independent risk factor 28, 30…”
Section: Discussionmentioning
confidence: 57%
“…Loewenberg-Weisband et al14 reported an incidence of 0.35% for severe (third- and fourth-degree) perineal tears, in singleton, term, vaginal deliveries. Independent predictors of OASIs were instrumental delivery (OR, 1.82; 95% CI, 1.25–2.65), prolonged second stage of labor (OR, 1.77; 95% CI, 1.19–2.61), primiparity (OR,3.19; 95% CI, 2.23–4.55), and episiotomy (OR, 1.69; 95% CI, 1.18–2.40).…”
Section: Resultsmentioning
confidence: 99%
“…25 However, the relationship between epidural analgesia and OASIS remains controversial. 3,[14][15][16] Epidural analgesia may increase the frequency of fetal malposition by affecting the likelihood of internal rotation, thereby increasing the rate of operative vaginal delivery. 25 In the present multivariate analysis accounting for confounding factors, epidural analgesia was found to be a protective factor against OASIS during vacuum delivery for all women and for the primiparous subgroup, but fetal malposition was a potential risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…

Objective: To investigate factors associated with obstetric anal sphincter injuries (OASIS) during vacuum delivery among Chinese women.

Methods:

A retrospective cohort study of Chinese women who underwent vacuumassisted vaginal delivery at a tertiary referral hospital in Taiwan between January 2010 and December 2016. [3][4][5][8][9][10][11][12][13][14][15][16] Many studies have reported that women of Asian ethnicity are at a higher risk of OASIS during vaginal delivery. Of the women who had a vacuum delivery, 1073 (34.16%) sustained OASIS, of whom 967 (90.12%) were primiparous.

…”
mentioning
confidence: 99%
See 1 more Smart Citation